Oxidative Stress In Patients With Acne Vulgaris Under Isotretinoin Treatment In Duhok, KRG, Iraq: Effect Of Vitamin C (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Acne Vulgaris (AV) is a common dermatological disorder. Evolving studies show that AV patients being treated with Isotretinoin mono therapy exhibit oxidative damage to the cell constituents, causing; lipid peroxidation and DNA damage. The purpose of the study was to examine the effect of vitamin C oral supplement on the oxidative stress in AV patients under Isotretinoin therapy.Method: An interventional prospective cohort study was done on forty AV patients, using a convenience sampling procedure, prescribed systemic Isotretinoin (0.3-0.4mg/kg/day), oral administration, for the first time; patients were divided into two groups of twenty subjects each with or without vitamin C given orally at (500mg/day). The oxidative damage biomarkers malondialdehyde (MDA) and 8-hydroxy-2’-deoxyguanosine(8-OHdG) levels were determined at baseline and after two months of treatment. Data were subjected to descriptive statistical analysis and Student’s-t-test.Results: Plasma MDA level was significantly increased in group A (Isotretinoin) when compared with the corresponding pre-treatment values. In group B (Isotretinoin plus vitamin C), the MDA level was decreased at p value=0.07 when compared with the corresponding pre-treatment values. However, serum 8-OHdG was not changed in both groups when compared to their corresponding pretreatment values.Conclusion: The addition of vitamin C was marginally effective in modulating the lipid peroxidation (MDA) seen in the AV patients under Isotretinoin therapy. Also, Isotretinoin lacks DNA damaging effect.